Perioperative concerns and outcomes in obstetric patients undergoing lower segment caesarean section in the wake of the COVID-19 pandemic: a retrospective analysis - Wani, Reena J.; Doshi, Kruti; Ansari, Sumayya; Bhatt, Mahin C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: In the current COVID-19 pandemic, pregnant women are considered high risk due to adverse maternal and foetal complications that are known to occur with antepartum viral infections. In addition to immunological changes in pregnancy that alter the response to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection, the disruption of routine antenatal services as a result of the pandemic has also adversely affected expectant mothers. Methods: We conducted this retrospective observational study as a comprehensive comparative analysis of the method of delivery in COVID positive women, the choice of anaesthesia and maternal and foetal outcomes in women undergoing lower segment caesarean sections with COVID infection as well as the COVID negative patients during the first wave of the pandemic. Results: The rate of caesarean section was comparable between the two groups. The rates of general and regional anaesthesia did not change with COVID positive status. However, we found that meconium-stained liquor with foetal distress as an indication for lower segment caesarean section (LSCS) was markedly higher in COVID positive patients. There was also a significantly higher requirement for ICU admission and ventilator support in the positive patients as a result of COVID-related complications. No significant difference was observed in the maternal and neonatal mortality rate between the two groups. Conclusions: In our experience, COVID-19 positive status did not impact the rate of LSCS, but significantly increased the need for intensive care.